The therapeutic role of alcoholic extract of fenugreek seeds on hypothyroidism state induced by thiourea and some blood parameters in adult male rabbits: Atyaf J. H. Al-Zyadi and Jawad K. Arrak - Al-Zyadi, Atyaf J. H. (The Iraqi Journal of Veterinary Medicine, 2015)
This study was carried out to investigate the effect of the alcoholic extract of fenugreek seed (Trigonella foenum graecum) on thyroid gland function in adult male rabbits exposed to thiourea that induce hypothyroidism state. Thirty adult male rabbits weighing 1500-2000 gm were used, and randomly divided into five equal groups (6 rabbits/group) and treated daily for 42 days as follows: First group (control), (T1) group were treated with alcoholic extract of fenugreek seed(200mg/ kg .B.W. orally), (T2) group were treated with thiourea (10 mg/kg. B.W. orally), (T3) group were treated once thiourea daily by (10 mg/ kg. B.W) and after (3) hours given alcoholic extract of fenugreek 200 mg/kg B.W., and (T4) group were treated once thiourea daily by (10mg /kg B.W) and after (3) hour given levothyroxine (10 ug/kg B.W). Blood samples were collected at (0, 14, 28 and 42) days of the experiment for measuring the concentration of hematological parameters. Blood parameters (HB, RBC, WBC, and PCV) were analyzed in this study. The results showed significant increase in (HB, RBC, WBC and PCV) in (T1) group significantly decreased in (T2) groups, while (T3 and T4) groups showed a significant increase of these parameters and their values appeared closely to control group. In conclusion supplementation of fenugreek seeds extract and levothyroxine have therapeutic effects against harmful effect of thiourea